Beradaptasi dengan Bencana: Strategi Beribadah Umat Islam dan Kristen di Tengah Pandemi Covid-19 - Hasse Jubba (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2021)
The Covid-19 pandemic has changed the worship pattern of religious people widely. Religious practices conducted regularly and carried out in special places have shifted. Communal worship practices that involve many worshippers are limited at home and involve limited people. This article aims to explain the form of a strategy of Muslims and Christians in carrying out their worship routines during the covid-19 pandemic. The data used as the basis for analysis are obtained through observations, interviews, and literature studies. This article shows that the change in the pattern of worship is the result of a state of emergency and the choice to continue to carry out obligations as a devoutly religious person. The limitations of the prayer room are circumvented by adjusting it to government policies. Policies on social distancing and compliance with health protocols are efforts to prevent the spread of the virus. In a religious context, it is part of an effort to save lives that must be obeyed. This article is still limited to discussions about changing the pattern of worship practices in two religious groups so it still needs further studies that also look at practices for adherents of other religions.